ASSOCIATION OF SOD2 (ALA16VAL), GPX4 (C718T), AND COL1A1 (C1997A) GENE POLYMORPHISMS WITH GOUTY NEPHROPATHY IN PATIENTS WITH GOUT - Rakhmatov Avazbek Mamat ugli, Jabbarov Ozimbay Otakhanovich (Ethiopian International Journal of Multidisciplinary Research, 2026)
Gouty nephropathy is one of the most important renal complications of gout. Oxidative stress, chronic inflammation, and extracellular matrix remodeling play an important role in its development. Therefore, candidate genes involved in antioxidant defense and connective tissue metabolism may influence susceptibility to renal involvement in patients with gout. To evaluate the association of SOD2 (Ala16Val), GPX4 (C718T), and COL1A1 (C1997A) gene polymorphisms with gouty nephropathy in patients with gout. A case-control study included 186 individuals. The control group consisted of 96 healthy subjects. Ninety patients with gout were divided into two groups: Group 1 included 45 patients with gout without gouty nephropathy, and Group 2 included 45 patients with gouty nephropathy. Allelic and genotypic frequencies of SOD2 (Ala16Val), GPX4 (C718T), and COL1A1 (C1997A) polymorphisms were compared between the clinical groups and the control group. Statistical analysis included χ² test, odds ratio (OR), and p values. The strongest associations were observed for the SOD2 Ala16Val polymorphism in patients with gouty nephropathy. In Group 2, the Ala allele showed a protective association (χ²=8.81; p=0.003; OR=0.34), whereas the Val allele was associated with increased risk (χ²=8.81; p=0.003; OR=2.95). The Ala/Ala genotype also demonstrated a protective effect (χ²=5.26; p=0.022; OR=0.38), while the Val/Val genotype was associated with a markedly increased risk of nephropathy (χ²=5.52; p=0.019; OR=9.27). For GPX4 C718T, significant differences in Group 2 were found for the C allele (χ²=4.00; p=0.045; OR=0.60) and T allele (χ²=4.00; p=0.045; OR=1.67), while genotype-level associations were not statistically significant. For COL1A1 C1997A, Group 2 showed a lower frequency of the C allele (χ²=8.81; p=0.003; OR=0.34), a higher frequency of the A allele (χ²=8.81; p=0.003; OR=2.95), a protective effect of the C/C genotype (χ²=5.26; p=0.022; OR=0.38), and a significant association of the A/A genotype with nephropathy risk (χ²=5.52; p=0.019; OR=9.27). The results indicate that SOD2 (Ala16Val), GPX4 (C718T), and COL1A1 (C1997A) polymorphisms are associated with susceptibility to gouty nephropathy in patients with gout, with the strongest association observed for SOD2 Ala16Val. These findings support the potential role of molecular genetic markers in identifying gout patients at increased risk of renal involvement.